Polypyrrole/Magnetic/Tea Waste Composites for PO43− Ions Removal: Adsorption-Desorption, Kinetics, and Thermodynamics Studies - Fatima Saleem; Haq Nawaz Bhatti; Amina Khan; Lamia Ben Farhat; Zainab Mufarreh Elqahtani; Norah Alwadai; Munawar Iqbal (Adsorption Science & Technology)
The polypyrrole (PPY/TW) and magnetic (MG/TW) composite with tea waste (TW) was prepared and used as an adsorbent for PO43− ions removal from aqueous media. The composite were characterized with SEM and FTIR techniques. Batch study was conducted to investigate the effect of different reaction parameters on the adsorption of PO43− ions. The native TW, PPY/TW, and MG/TW showed the PO43− ions removal of 7.2, 7.3, and 7.9 (mg/g), respectively, using 0.05 g adsorbent dose and 10 mg/L initial concentration of PO43− ions at pH of 6, 10, and 3, respectively, and equilibrium was reached in 90 min. Kinetics and isotherm models were employed on the PO43− ions adsorption data and PO43− ions adsorption followed the pseudo-second order kinetics, intraparticle diffusion, and Langmuir isotherm models. Thermodynamics analysis reveals an exothermic process and spontaneous adsorption of PO43− ions on the composites. Results revealed that the magnetic and polypyrrole composites with tea waste have auspicious potential as an adsorbent and this class of the composites can be utilized for the removal of PO43− ions from the effluents.